PENGEMBANGAN KREATIVITAS ANAK MELALUI KEGIATAN EKSPLORASI - Faizah, Faizah (Thufuli, 2019)
The purpose of this study was to understand the process of developing the creativity of kindergarten-aged children through exploration activities at Pertiwi Kindergarten. It was using a qualitative descriptive research method. This research prepares, understands and analyzes exploration activities as an effort to develop children's creativity. The results of the study show; the concept of exploration activities at the Pertiwi Kindergarten was carried out as a substitute for learning activities and adapted to the theme of learning. The activity forms such as; gardening, playing water, playing sand, animal exploration, and rice harvest exploration. Its implications are children's information insight is increasingly widespread, growing love toward the environment. Children become more creative and critical, and foster an attitude of children independence and responsibility.Keywords: Child Creativity Development, Exploration Activities.